Cirurgia de adenoidectomia e amigdalectomia no serviço público do interior do Paraná - Santos, Flávia Soares dos (2017)
The hypertrophy of the palatine and pharyngeal tonsils is common in childhood, being one of the most frequent problems of the otorhinolaryngologist's office. Tonsil hypertrophy causes constant oral breathing and this respiratory mode leaves the patient exposed to numerous alterations, such as craniofacial, orthognathic, chewing, swallowing, speech disorders and dental arch deformities, which may affect children's quality of life. In addition, tonsillar hypertrophy is the main cause of upper airway obstruction and is responsible for sleep disorders. The final procedure to solve the presence of hypertrophic tonsils is surgical, of elective scope. The present study aims to characterize the demand of children with adenoid and tonsil hypertrophy and to understand the referral process in cases of need for adenoidectomy and tonsillectomy in the context of the Unified Health System in the municipality of Irati-PR and the AMCESPAR region. In addition, the objective is to analyze preventive actions of the surgical procedures in question. The methodology used refers to a quantitative and qualitative approach. The quantitative part has a descriptive characteristic in which it is possible to characterize the profile of the patients submitted to adenoidectomy and tonsillectomy in the year 2015. The qualitative part refers to the vision of the professionals involved, obtained from the semi- structured interviews with the physicians otorhinolaryngologists who work via SUS in the municipality of Irati. To analyze the qualitative data the content analysis approach was adopted. The results pointed to the fragility in a harmonious conduct among professionals. The professionals interviewed manifest a positive conception regarding the surgical procedure as well as the impact on the quality of life of the subject. The demand for surgeries prevail for males, with a mean of 6 years, the most applied surgical technique is associated dissection and curettage, the average time of surgery is 52 minutes in the time they remain in the hospital is approximately 13 hours, it was verified 05 records in medical records that had complications in the postoperative period. The study evidences the need to invest in protocols and lines of care in the area of otorhinolaryngology, especially regarding diagnoses and referrals for surgery of palatine and pharyngeal tonsils.